2021
DOI: 10.48550/arxiv.2109.07320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Error estimation and adaptivity for stochastic collocation finite elements Part I: single-level approximation

Abstract: A general adaptive refinement strategy for solving linear elliptic partial differential equation with random data is proposed and analysed herein. The adaptive strategy extends the a posteriori error estimation framework introduced by Guignard & Nobile in 2018 (SIAM J. Numer. Anal., 56, 3121-3143) to cover problems with a nonaffine parametric coefficient dependence. A suboptimal, but nonetheless reliable and convenient implementation of the strategy involves approximation of the decoupled PDE problems with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The numerical results presented in [5] demonstrate the effectivity and robustness of our error estimation strategy as well as the utility of the error indicators guiding the adaptive refinement process. The results in [5] also showed that optimality of convergence is difficult to achieve using a simple single-level approach where a single finite element space is associated with all active collocation points. The main aim of this contribution is to see if optimal convergence rates can be recovered by computing results using a multilevel implementation of the algorithm outlined in [5].…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…The numerical results presented in [5] demonstrate the effectivity and robustness of our error estimation strategy as well as the utility of the error indicators guiding the adaptive refinement process. The results in [5] also showed that optimality of convergence is difficult to achieve using a simple single-level approach where a single finite element space is associated with all active collocation points. The main aim of this contribution is to see if optimal convergence rates can be recovered by computing results using a multilevel implementation of the algorithm outlined in [5].…”
Section: Introductionmentioning
confidence: 78%
“…The combination of adaptive sparse grid methods with a hierarchy of spatial approximations is a relatively new development, see for example, [12,13]. In our precursor paper [5] (part I), we extended the adaptive framework developed by Guignard & Nobile [10] and presented a critical comparison of alternative strategies in the context of solving a model problem that combines strong anisotropy in the parametric dependence with singular behavior in the physical space. The numerical results presented in [5] demonstrate the effectivity and robustness of our error estimation strategy as well as the utility of the error indicators guiding the adaptive refinement process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations